Artikel Tentang Perencanaan dan Pengembangan Bisnis - Aldo Nahason Pasca; Moh. Iqbal Prasetyo Ritonga; M. Afif Zaky Akmal; Rusdi Hidayat N; Maharani Ikaningtyas (ManBiz: Journal of Management and Business, 2024)
The important process known as business planning and development allows an organization to establish the strategies, goals, and tactics necessary to grow and succeed in the long term. Businesses are faced with many complex challenges in the current era of globalization, ranging from intense competition to rapid market changes. Therefore, careful business planning is essential to anticipate changes and take advantage of emerging opportunities. In this abstract, business planning and development is very important in today's dynamic business environment. Internal and external environmental analysis, goal setting, strategy development, resource allocation, and implementation are the main steps in the business planning process, which will be discussed thoroughly. In addition, this abstract will show how leadership, innovation, and information technology help business planning and development well. Organizations can optimize performance, increase competitiveness, and better face challenges by emphasizing holistic and sustainable business planning and development. Understanding market, consumer and industry trends is important amidst global uncertainty. Therefore, this abstract emphasizes how important it is to monitor the business environment and be flexible when changing business planning strategies to adapt to changes.